PENGARUH PENEMBAKAN LASERPUNKTUR PADA TITIK REPRODUKSI ITIK CAMPBELL (Anas platyrhynchos domesticus) BETINA TERHADAP PRODUKTIVITAS TELUR - Renata, Sena Sangga; Suprayogi, Tri Wahyu; Estoepangestie, A.T Soelih; Adikara, R.T. Santanu; Tehupuring, Benjamin Chr.; Hidanah, Sri (Ovozoa: Journal of Animal Reproduction, 2019)
The technology of laserpuncture in livestock is an acupuncture technique using Laser (Light Amplification by Stimulated Emission of Radiation) that is fired at acupuncture points as biological receptors that are related to organs that can provide stimulatory effects. This research was conducted in the laboratory of Airlangga University for 30 days using a sample of 18 cambell ducks divided into 3 treatments and laser shot with 3 days interval. Treatment 0 as control, treatment 1 got laser treatment dose 0,2 joule and treatment 2 got laser treatment dose 0,5 joule. On the final result of the eggs that have been in the production of duck research for 29 days. P2 given laser shootings with a dose of 0.5 joule yielded more eggs with 158 grains compared to P1 given laser shootings with a dose of 0.2 joules yielding 126 grains and P0 with inactivated laser yielding a total of 86 grains. The conclusion of this study is the shooting of laserpuncture dose of 0.2-0.5 joule can increase egg productivity